The Effect of Sustainability Report Disclosure and Financial Performance on Firm Value with Dividend Policy as a Mediating Variable - Alomoy, Sarlinda Elizabeth; Badera, I Dewa Nyoman (Dinasti Publisher, 2025)
This study aims to examine the effect of sustainability reports and financial performance on firm value, with dividend policy as a mediating variable. The population in this study consists of companies listed on the LQ45 index, with samples selected using purposive sampling techniques, resulting in 21 companies during the five-year observation period (105 observations). Data analysis was conducted using path analysis. The results of the study indicate that sustainability reports do not influence dividend policy and have a negative effect on firm value. Additionally, dividend policy does not mediate the relationship between sustainability reports and firm value. Conversely, financial performance has a positive effect on dividend policy and firm value. Dividend policy is also found to mediate the influence of financial performance on firm value.